Effects of Ammonium Phosphate on Structure of Cell and Carb on Layer after Burned of Polyurethane-imide Foams - ZHANG Qi; LIU Juan; WANG Ying; SANG Xiao-ming (Cailiao gongcheng, 2017)
Using ammonium phosphate as flame retardant,polyurethane-imide foams were synthesized via PI pre-polymer method. The effect of APP on the cell structure, thermal stability and carbon layer morphology were analyzed by polarizing microscope,SEM and TGA. The effect of cell structure change on carbon layer morphology was focused and discussed and the formation process of carbon layer was simulated. The results show that cell diameter drops sharply from 690.25μm to 277.83μm, the foam density increases with the increasing addition of APP;the addition of APP makes char yield increased by 30%; the cell wall and peak respectively expand into rod-like and spherical carbon layer, but the cell films burn into holes. Furthermore, the sizes of rod-like and spherical carbon layer increase, but the holes decrease with the increasing addition of APP.